Applying Decision Tree and Bibliometric Analysis: The Analysis of Digital Governance Determinants - Kunviroteluck, Benjawan; Kongthon, Alisa; SaeLim, Patipan (Journal of Current Science and Technology, 2023)
Digital governance plays a crucial role in leading organizations in their digital transformation process. This paper aims to explore the analysis of digital governance determinants through the application of decision tree and bibliometric analysis techniques. Understanding these factors can help organizations in developing effective digital governance initiatives and strategies. Bibliometric analysis is utilized to identify new trends and overall research landscape of digital governance. K-means clustering and decision tree are then used to identify key determinants of effective digital governance. Our results show that leadership is the most initial important factor. In addition, to enhance digital governance to the highest level, organizational culture that is driven from the leader is also another important factor. The findings of this study yield insights for practitioners and managers who seek to improve their digital governance practices.